2013
DOI: 10.1007/s10567-013-0130-6
|View full text |Cite
|
Sign up to set email alerts
|

Age at Adoption from Institutional Care as a Window into the Lasting Effects of Early Experiences

Abstract: One of the major questions of human development is how early experience impacts the course of development years later. Children adopted from institutional care experience varying levels of deprivation in their early life followed by qualitatively better care in an adoptive home, providing a unique opportunity to study the lasting effects of early deprivation and its timing. The effects of age at adoption from institutional care are discussed for multiple domains of social and behavioral development within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
94
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 112 publications
(188 reference statements)
12
94
0
2
Order By: Relevance
“…This study supports previous international research which argues that age at adoption and pre-adoption experience influence a child's post-adoption attachment, adjustment and ongoing development, and these children may need additional assistance at school (Gunnar et al, 2007;Julian, 2013;Rutter, 1998;Rutter, Colvert et al, 2007;Sharma, McGue, & Benson, 1996a;Verhulst, 2000). While some distinctions have been made between the long-term educational and behavioural outcomes for children reared in better quality orphanages in some Asian countries (Dalen, 2002;Tan et al, 2007Tan et al, , 2010, the majority of studies have focused predominantly on the adoption of children from significantly deprived institutions in Eastern Europe (Albers et al,.…”
Section: Significance Attachment and Traumasupporting
confidence: 89%
See 2 more Smart Citations
“…This study supports previous international research which argues that age at adoption and pre-adoption experience influence a child's post-adoption attachment, adjustment and ongoing development, and these children may need additional assistance at school (Gunnar et al, 2007;Julian, 2013;Rutter, 1998;Rutter, Colvert et al, 2007;Sharma, McGue, & Benson, 1996a;Verhulst, 2000). While some distinctions have been made between the long-term educational and behavioural outcomes for children reared in better quality orphanages in some Asian countries (Dalen, 2002;Tan et al, 2007Tan et al, , 2010, the majority of studies have focused predominantly on the adoption of children from significantly deprived institutions in Eastern Europe (Albers et al,.…”
Section: Significance Attachment and Traumasupporting
confidence: 89%
“…Numerous studies have found that older age at adoption, and corresponding length of time spent in an institutional setting versus time in an adoptive family, makes a difference to children's long term developmental outcomes (Julian, 2013).…”
Section: Age At Adoption and Time In Familymentioning
confidence: 99%
See 1 more Smart Citation
“…projection as defense mechanism, dual relationship). Selective coding was articulated around the research question in regard to narcissistic identity pathologies as an outcome of early trauma, due to severity of caregiving deprivation, firstly roughly estimated by age at adoption [19] and then by group. Key categories which could embed groups of categories were defined.…”
Section: Methodsmentioning
confidence: 99%
“…What is also clear is that length of preadoption time and severity of caregiving deprivation emerge as two predicting factors of delays in the development of neurological and age-level motor skills, and that the simple enrichment of the adopted child's environment following adoption proves insufficient to repair such damage beyond certain critical ages or sensitive periods [10,[15][16][17][18]. These sensitive periods and cutoff ages differ depending on the institution and country of origin according to the severity of deprivation to which the child has been exposed [19].…”
Section: Introductionmentioning
confidence: 99%